Nutritional sciences from fundamentals to food - McGuire, Michelle (Australia Cengage Learning, 2018)
"Nutritional Sciences: from Fundamentals to Food, 3rd Enhanced Edition clearly explains the scientific principles underlying nutrition while incorporating applications to promote a complete understanding of core concepts. This integrated approach provides a strong science foundation in a context relevant to your daily life and career. Supported by an impressive visual design, engaging case studies and interactive digital resources, Nutritional Sciences offer a unique, balanced program for learning"--Provided by publisher.
Keywords: Nutrition -- Textbooks